1992
DOI: 10.1093/jn/122.12.2330
|View full text |Cite
|
Sign up to set email alerts
|

Prickly Pear (Opuntia sp.) Pectin Reverses Low Density Lipoprotein Receptor Suppression Induced by a Hypercholesterolemic Diet in Guinea Pigs

Abstract: The effects of prickly pear pectin on plasma LDL metabolism were investigated by feeding guinea pigs either a diet containing 15 g/100 g lard and 0.25 g/100 g cholesterol (LC diet) or the LC diet in which cellulose was partially replaced (2.5 g/100 g) by prickly pear pectin (LC-P diet). The LC-P diet lowered plasma LDL cholesterol concentrations by 33% (P < 0.001). Low density lipoprotein composition was modified by intake of prickly pear pectin; the relative percentages of free and esterified cholesterol were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…In a series of studies with Guinea pigs, Fernµndez et al [173 -175] demonstrated that the reduction of blood lipids triggered by isolated pectin from Opuntia was due to the enhanced binding of bile acid. It was concluded that through reduced bile absorption in the colon the enterohepatic circle was disrupted [173,174]. In a followup study, the same authors presented evidence that the lowdensity lipoprotein (LDL)-catabolism was considered to be more important than the modulation and de novo synthesis in the liver [175].…”
Section: Anti-hyperlipidemic Propertiesmentioning
confidence: 99%
“…In a series of studies with Guinea pigs, Fernµndez et al [173 -175] demonstrated that the reduction of blood lipids triggered by isolated pectin from Opuntia was due to the enhanced binding of bile acid. It was concluded that through reduced bile absorption in the colon the enterohepatic circle was disrupted [173,174]. In a followup study, the same authors presented evidence that the lowdensity lipoprotein (LDL)-catabolism was considered to be more important than the modulation and de novo synthesis in the liver [175].…”
Section: Anti-hyperlipidemic Propertiesmentioning
confidence: 99%
“…Other dietary-fibre sources, such as psyllium and USP, were also found to have a cholesterol-lowering effect only when given in the presence of dietary cholesterol (Abbey et al 1993;Horton et al 1994). These dietary fibres, when fed together with cholesterol, increase the LDL-receptor expression in guinea pigs, thereby leading to increased uptake of LDL and lowering plasma cholesterol levels (Fernandez et al 1992). The mechanism of the regulation of hepatic LDL-receptor activity by rhubarb fibre under diabetic conditions is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Table 18.2 summarizes the most remarkable results and the plant sources analyzed for the performed studies. Fernandez et al ( 1992 ); guinea pigs, Fernandez et al ( 1994 ) Opuntia robusta fruits Nondiabetic hyperlipidemic humans, Wolfram et al ( 2002 ) Opuntia fi cus-indica cladode Rats, Galati et al ( 2003a , b ) Opuntia fi cus-indica s eed oil Rats, Ennouri et al ( 2006a ) Opuntia fi cus-indica seeds Rats, Ennouri et al ( 2006b ) Cactus pear seeds and oil Rats, Ennouri et al ( 2007 ) Opuntia fi cus-indica var. saboten Mice, Oh and Lim ( 2006 ) Liver protection…”
Section: Medicinal Propertiesmentioning
confidence: 99%